1980
DOI: 10.1159/000123066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Discrete Lesions of Preoptic and Suprachiasmatic Structures in the Female Rat

Abstract: The purpose of this study was to determine which specific structures within the medial preoptic-anterior hypothalamic area are necessary to maintain cyclic ovulation in the rat, and to define the deficit(s) in the feedback regulation of gonadotropin secretion associated with lesions that result in anovulation. Large (∼1.1 mm dia.) or small (∼0.7 mm dia.) electrolytic lesions were placed in several loci within preoptic, anterior hypothalamic and suprachiasmatic areas in regularly cycling adult female rats. Larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
114
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(124 citation statements)
references
References 14 publications
(17 reference statements)
9
114
0
1
Order By: Relevance
“…28,59 Disruption of biological rhythms across the HPO axis: animal studies Several pioneer studies have shown that SCN ablation or lesions in rats result in irregular estrous cycles and the inhi bition of LH surge and of ovulation. 23,60,61 These results have been confirmed by recent studies of core clock gene mutants and mutant cell lines.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…28,59 Disruption of biological rhythms across the HPO axis: animal studies Several pioneer studies have shown that SCN ablation or lesions in rats result in irregular estrous cycles and the inhi bition of LH surge and of ovulation. 23,60,61 These results have been confirmed by recent studies of core clock gene mutants and mutant cell lines.…”
supporting
confidence: 68%
“…In other words, the timing of the LH surge, and therefore the timing of ovulation, is highly determined. 23,24 As for other seasonal and circadian rhythms, the timing of reproductive function in mammals, including humans, is also orchestrated mainly by the SCN as part of the hypothalamuspituitary-ovary (HPO) axis. The functioning of the HPO axis is a good example of the tight interconnections and circadian synchronization between neural, endocrine, and neuro endocrine signals that result in the ovarian cycle, ie, the main component of reproduction in female mammals.…”
mentioning
confidence: 99%
“…Second, there is compelling evidence that the GnRH/LH surge is generated by E-sensitive neurons whose cell bodies reside in the AVPV and are activated by a circadian signal from the suprachiasmatic nucleus (SCN) (Gu and Simerly, 1997;de la Iglesia and Schwartz, 2006). Lesions of the AVPV block spontaneous and steroidinduced LH surges (Wiegand et al, 1978(Wiegand et al, , 1980Terasawa et al, 1980;Wiegand and Terasawa, 1982;Ronnekleiv and Kelly, 1986;Ronnekleiv and Kelly, 1988;Le et al, 1999). Third, the AVPV is sexually differentiated, with females having greater numbers of cells than males (Simerly, 1998), and the surge mechanism is only present in the female rodents (Pfeiffer, 1936;Barraclough, 1961;Gogan et al, 1980;Corbier, 1985;Hoffman et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Timed preovulatory activation of GnRH neurons depends mainly on two factors: a rising concentration of E2 during the follicular phase of the oestrous cycle and a circadian timekeeping system. The master circadian pacemaker in mammals is located in the suprachiasmatic nuclei (SCN) of the hypothalamus, and classic experiments have shown that surgical ablation of SCN results in disruption of the oestrous cycle in rats 33,34 . Mutations in key circadian rhythm genes such as Clock or Bmal1 in mice affect female reproductive function resulting in an extended and irregular oestrous cycle 35,36 .…”
Section: Discussionmentioning
confidence: 99%